Ideological Tripolarization, Partisan Tribalism and Institutional Trust: The Foundations of Affective Polarization in the Swedish Multiparty System. (16th January 2021) - Reiljan, Andres; Ryan, Alexander
Abstract : Currently, very little is known about the individual level foundations of affective polarization outside the US context. This paper addresses this research gap by exploring the predictors of affective polarization in Sweden, using nationally representative survey data. From 2010 till the 2018 elections, the Swedish multiparty system was divided into two affectively converged mainstream party blocs that were moderately polarized between each other, and an asymmetrically polarized populist right party that invoked significantly more hostility from the supporters of mainstream parties than vice versa. To unpack the foundations of affective polarization in such a tripolar configuration, we employ a methodological approach that distinguishes not just between in‐ and outparties but also in‐ and out‐blocs, and separates different conflict dimensions. We find that: (1) voters with stronger partisan identities and more extreme political attitudes exhibit higher levels of affective polarization. The latter, however, is a better predictor of direct dislike towards political opponents; (2) the effects of political attitudes correspond to the tripolar nature of the party system: while affective polarization between the centre‐right and ‐left blocs is mostly driven by socioeconomic positions, the hostility towards Sweden Democrats links predominantly to cultural issues, most notably immigration; (3) institutional trust has a two‐edged relationship with affective polarization: populist right voters that trust the country's central institutions more, are less polarized towards mainstream blocs, whereas among centre‐right voters, higher trust associates with stronger animosity towards Sweden Democrats. We believe that these findings could have broad implications for affective polarization research in multiparty systems.